Psychological aspects in children and adolescents with dyslexia: a systematic review - Dantas Pereira, Mara; Pereira da Silva, Joilson (Revista Interamericana de Psicología/Interamerican Journal of Psychology, 2023)
This study aimed to understand the psychological aspects related to dyslexia in the childhood and adolescence phases within the school context, using international productions published between 2009 and 2020. A systematic review of the literature was carried out using the following search strategy: ("Dyslexia" OR "Dyslexia, Developmental" OR "Disorders, Developmental Reading" OR "Reading Disorders" OR "Reading Disability, Developmental") AND ("Child" OR "Children") AND ("Mental Health" OR "Anxiety" OR "Depression" OR "Self Esteem") AND ("School" OR "Primary Schools" OR "Secondary School"), in the PsycINFO, PubMed, WoS and Scopus databases. A total of three hundred and seventeen files were found, with the final bank of analysis consisting of eleven studies. The results showed that the dyslexic condition experienced in childhood and adolescence has repercussions on various psychological aspects of the subject, as they are more likely to develop symptoms of anxiety and depression, negatively affecting the self-esteem of these individuals. Despite this, it is emphasized the importance of new studies involving only one phase of the life cycle of the two addressed, in order to provide better understanding of how the psychological aspects manifest themselves in dyslexic individuals according to their age group.